Governance and Sustainable Urban Transport in the Americas - Mercier, Jean; Tremblay-Racicot, Fanny; Carrier, Mario; Duarte, Fábio (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This volume explores the governance patterns of three cities of the Americas, Seattle, Montreal, and Curitiba, which all present different but interesting cases in dealing with sustainable urban transport challenges. The authors study empirical data from these three cities to analyze how specific governmental and policy instruments (planning, consultation and market mechanisms for example) were implemented in each case. Through concepts coming from policy studies and sociology, for example, such as path dependency, institutional culture and transaction costs, the three cities are also looked at in a broader perspective in order to better understand how they deal differently with their common challenges.